Chronic Ultraviolet Irradiation to the Skin Dysregulates Adrenal Medulla and Dopamine Metabolism In Vivo - Hye-Sun Lim; Kyeong-No Yoon; Jin Ho Chung; Yong-Seok Lee; Dong Hun Lee; Gunhyuk Park (MDPI AG, 2021)
Ultraviolet (UV) radiation has a strong biological effect on skin biology, and it switches on adaptive mechanisms to maintain homeostasis in organs such as the skin, adrenal glands, and brain. In this study, we examined the adaptation of the body to repeated bouts of UVB radiation, especially with respect to the catecholamine synthesis pathway of the adrenal glands. The effects of UVB on catecholamine-related enzymes were determined by neurochemical and histological analyses. To evaluate catecholamine changes after chronic excessive UVB irradiation of mouse skin, we examined dopamine and norepinephrine levels in the adrenal glands and blood from UV-irradiated and sham-irradiated mice. We found that chronic excessive UVB exposure significantly reduced dopamine levels in both tissues but did not affect norepinephrine levels. In addition, UVB irradiation significantly increased the levels of related enzymes tyrosine hydroxylase and dopamine-β-hydroxylase. Furthermore, we also found that apoptosis-associated markers were increased and that oxidative defense proteins were decreased, which might have contributed to the marked structural abnormalities in the adrenal medullas of the chronically UVB-irradiated mice. This is the first evidence of the damage to the adrenal gland and subsequent dysregulation of catecholamine metabolism induced by chronic exposure to UVB.